Ethics of management - "Hosmer, Larue Tone" (New Delhi, 1989)
It is often said that ethics is essential for leadership; Hosmer argues that leadership is also essential for ethics. The theme of The Ethics of Management, 7e, is that business firms today operate in a competitively- intense, technologically-complex and culturally-diverse global economy. Pressures to dodge issues and cut corners are greater than ever before. The Ethics of Management provides a very explicit three-part framework to analyze those problems by combining economic outcomes, legal requirements and ethical principles. Students will learn how to convincingly present their moral points of view to others in order to jointly serve their companies, protect their careers, and improve their societies.
Keywords: Management